Addition of Coffee Pulp Flour to Local Feed on Grower Phase Pig Production in Ngada Regency - Bhae, Christianus Yoseph Ngiso; Rembo, Egidius; De Ornay, Tito A.E.M. (Jurnal Biologi Tropis, 2024)
Pig farming is highly needed by the Bajawa community in their daily lives, so the Bajawa people see the necessity of pig farming not only for its social value but also because it is highly valuable due to its close connection with local customs and cultural rituals. The nutritional content of coffee fruit husks, which is almost similar to fine flour, and their availability, which has not yet been fully utilized, provide a significant opportunity to be used as feed material. The research aims to determine the extent of the effect of using coffee husk flour as a partial substitute for fine flour in feed on feed consumption, weight gain, and feed efficiency in grower phase pigs. This study uses a randomized block design with 4 types of feed (R0, R1, R2, R3) as treatments and 4 groups of pigs as repetitions, with each group consisting of 3 pigs. The results show that the use of coffee husk flour as a substitute for part of the fine flour in pig feed increases feed consumption, weight gain, and feed conversion in pigs during the grower phase. The best treatment is R3 (0% fine bran + 25% coffee husk flour). The results of the ANOVA test indicate that the provision of feed with coffee husk flour shows differences in feed consumption, weight gain, and feed conversion in pigs among each treatment with a significance value of 0.000. The Duncan post hoc test shows significant differences in feed consumption, weight gain, and feed conversion in pigs among each feed treatment.